The measurement of inequality in the reduction of child mortality in Peru: La medicion de la desigualdad en la reduccion de la mortalidad infantil en el Peru - Figueroa Mujica, Ramón (2019)
Objective: To define the feasibility of determining inequality in infant mortality according to the mother's educational level and according to the wealth quintile of the 1991-2013 period, considering the level of precision of said rates. Methods: The type of study was quantitative and observational, with a crosssectional design based on repeated surveys. The data from the ENDES surveys corresponding to those of 1991, 1992, 1996, 2000, 2008 and 2013 were used. Infant mortality was determined using the direct method of synthetic cohort life tables. The level of precision of the estimates was determined by the relative error. Results: It´s observed that the level of precision of the estimates of these general rates has fluctuated between good and very good in the 1991-1992, 1996 and 2000 surveys; however, in 2008 and 2013 they only reach an acceptable level. Infant mortality rates tend to be lower as the mother's educational level improves, as well as the wealth quintile and elsewhere exists among successive surveys a tendency to reduce infant mortality in different categories. Conclusion: It is not feasible to determine the inequality of the measurement of Infant Mortality according to the mother's educational level and according to the wealth quintile in the period 1991-2013, because the sample size has not been increased, depending on the decreased mortality.